Quantitative Imaging of Cerebral Thromboemboli In Vivo: The Effects of Tissue-Type Plasminogen Activator. Issue 5 (May 2017) - Kim, Dong-Eog; Kim, Jeong-Yeon; Schellingerhout, Dawid; Ryu, Ju Hee; Lee, Su-Kyoung; Jeon, Sangmin; Lee, Ji Sung; Kim, Jiwon; Jang, Hee Jeong; Park, Jung E.; Kim, Eo Jin; Kwon, Ick Chan; et al.
Abstract : Background and Purpose—: Quantitative imaging for the noninvasive assessment of thrombolysis is needed to advance basic and clinical thrombosis-related research and tailor tissue-type plasminogen activator (tPA) treatment for stroke patients. We quantified the evolution of cerebral thromboemboli using fibrin-targeted glycol chitosan–coated gold nanoparticles and microcomputed tomography, with/without tPA therapy. Methods—: We injected thrombi into the distal internal carotid artery in mice (n=50). Fifty-five minutes later, we injected fibrin-targeted glycol chitosan–coated gold nanoparticles, and 5 minutes after that, we treated animals with tPA or not (25 mg/kg). We acquired serial microcomputed tomography images for 24 hours posttreatment. Results—: Thrombus burden at baseline was 784×10 3 ±59×10 3 μm 2 for the tPA group (n=42) and 655×10 3 ±103×10 3 μm 2 for the saline group (n=8; P =0.37). Thrombus shrinkage began at 0.5 to 1 hour after tPA therapy, with a maximum initial rate of change at 4603±957 μm 2 /min. The rate of change lowered to ≈61% level of the initial in hours 1 to 2, followed by ≈29% and ≈1% in hours 2 to 3 and 3 to 24, respectively. Thus, 85% of total thrombolysis over 24 hours (≈500 μm 2, equivalent to 64% of the baseline thrombus burden) occurred within the first 3 hours of treatment. Thrombus burden at 24 hours could be predicted at around 1.5 to 2 hours. Saline treatment was not associated with significant changes in the thrombus burden. Infarct size was smaller in the tPA group versus saline group (18.1±2.3 versus 45.8±3.3 mm 2 ; P <0.01). Infarct size correlated to final thrombus burden ( r =0.71; P <0.01). Time to thrombolysis, completeness of thrombolysis, and tPA therapy were independent predictors of infarct size. Conclusions—: Thromboembolic burden and the efficacy of tPA therapy can be assessed serially, noninvasively, and quantitatively using high-resolution microcomputed tomography and a fibrin-binding nanoparticle imaging agent. Abstract : Supplemental Digital Content is available in the text.